Programming microsoft visual C++ - Kruglinski David J; Shepherd George; Wingo Scot (Bangalore WP, 2001)
Newly expanded and updated for Microsoft Visual C++ 6.0, it offers even more of the detailed, comprehensive coverage thatts consistently made this title the best overall explanation of the capabilities of this powerful and complex development tool, inclu
Keywords: C++(Computer program language); Computer programming; Computer programming languages